Laporan Penelitian Analisis Kinerja Keuangan Koperasi Konsumen Pinang Sepakat Sejahtera Periode 2022-2024 - Widya Sulistya; Keysa Dwina Syalsabila; Kania Marsilla Lumban Gaol; Hadli Lidya Rikayana (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze and assess the financial performance of the Pinang Sepakat Sejahtera Consumer Cooperative (KKPSS) over a three-year period, specifically from 2022 to 2024. As a Consumer Cooperative operating in the fashion, culinary, and handicraft sectors in Tanjungpinang, it plays a vital role in improving members' welfare and contributing to the local economy. A measurable financial performance analysis is crucial to evaluate management's efficiency in handling assets and capital to maximize profit. The research method is quantitative descriptive, focusing on financial ratio analysis: Liquidity (Current Ratio), Solvency (Total Asset to Debt Ratio), and Profitability (Return on Equity or ROE). Secondary data from KKPSS financial statements (2022–2024) serve as the primary source. Overall, the research concludes that KKPSS's financial performance is in a good category. The Solvency performance consistently falls into the Healthy category, indicating that the cooperative's total assets can adequately cover its total liabilities. The Profitability performance (ROE) is categorized as Quite Healthy, fluctuating between 14% and 19%, suggesting the need for SHU optimization. However, the Liquidity aspect is identified as Unhealthy. The main issue with Liquidity stems from a large amount of idle or unproductive cooperative assets within the current asset structure, which creates a pseudo-liquidity and hinders real cash availability. The Cooperative is advised to immediately review, activate, or divest these unproductive assets, and enhance product innovation supported by member participation to optimize the Surplus/Deficit for Members' Operations (SHU).